From Such Great Heights - Pehl, Matthew (Labour / Le Travail, 2017)
This article reviews "Labor’s Love Lost: The Rise and Fall of the Working-Class Family in America," by Andrew J. Cherlin, "Hillbilly Elegy: A Memoir of a Family and Culture in Crisis," by J.D. Vance, "Fighting for Total Person Unionism: Harold Gibbons, Ernest Calloway, and Working-Class Citizenship," by Robert Bussel, "Conservative Counterrevolution: Challenging Liberalism in 1950s Milwaukee," by Tula A. Connell, and "Reframing Randolph: Labor, Black Freedom, and the Legacies of A. Philip Randolph," edited by Andrew E. Kersten and Clarence Lang.